Professional competencies in speech-language pathology and audiology - Dantuma, Tonya (Burlington, MA : Jones & Bartlett Learning, 2021)
'Professional Competencies in Speech-Language Pathology and Audiology is designed for the professional issues course at the graduate level in a speech-language pathology or audiology program. ASHA recently updated the curriculum standards for master's level programs to include a list of professional competencies, identifying a need for direct instruction in professional competencies for SLP students. The purpose of this text will be to provide that direct instruction in professional competency and soft-skills. Topics such as cultural competence, professional duties, collaborative practices, clinical reasoning and evidence-based practices, and effective communication skills will be covered'--
What is an ASHA Professional? / Dr. Tonya Dantuma -- Adulting: Being a Professional in the Workplace / Dr. Teri Clemons & Dr. Tonya Dantuma -- Non-verbal Communication: Understanding and Communicating Well / Dr. K. Arianna Molloy & Dr. Tonya Dantuma -- Professional Written Communication / Dr. Tonya Dantuma -- Counseling in Speech-Language Pathology and Audiology / Dr. Matthew H. Rouse -- Cultural Competency: A Journey to Self-Awareness Through Cultural Humility / Stephanie Calley & Dr. Tonya Dantuma -- Collaboration: Working with Clients, Families, and Colleagues / Laureen Mgrdichian, M.B.A. & Dr. Tonya Dantuma -- Supervision: Supervising and Being Supervised / Dr. Teri Clemons and Dr. Tonya Dantuma -- Cultivating Resilience Against Stress, Compassion Fatigue and Burnout / Dr. K. Arianna Molloy & Dr. Tonya Dantuma -- The Growing Professional: Professional Development and Leadership / Dr. Carrie Stockton & Dr. Tonya Dantuma -- Understanding and Embracing a Changing Profession / Beth Nishida, Catilyn Kobata & Dr. Tonya Dantuma.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 13, 2020).
WorldCat record variable field(s) change: 650
Keywords: Speech therapy -- Study and teaching; Audiology -- Study and teaching; Speech disorders; Language disorders; Hearing disorders; Speech Disorders; Hearing Disorders; Language Disorders; Audiology -- Study and teaching; Language disorders; Speech disorders; Speech therapy -- Study and teaching; Electronic books